The progress in development of the 3D courseware / Mohd Husaiful Hamzah Shukor - Hamzah Shukor, Mohd Husaiful (2005)
Progress in development of the 3D courseware mean that the increase or decrease of 3D courseware project in year 1999 to year 2005 where is based on information found in nine selected companies in Kuala Lumpur and Sclangor area. Progress in development of the 3D courseware is depend on successful project in one company, how many a company get project, type of product and demanding from client. The need of methodology in this research is by collecting primary data and secondary data. Primary data collected by questionnaires give to nine selected companies and secondary data is based on journals, online articles, books and magazines. In this methodology, the collected data from primary and secondary will be analyzed to become information. The finding in this research is concerning on demographic profile company, accomplishment project, skill and knowledge company and demand from client. After get the finding, the summarization of entire research is done and come out with a guideline to developer or other person who want to involve in development on 3D courseware so that developer will produce a successful project.